2007
DOI: 10.3767/000651907x609115
|View full text |Cite
|
Sign up to set email alerts
|

Notes on the genus Argostemma (Rubiaceae) of the Malay Peninsula and Peninsular Thailand

Abstract: SUMMARYThe genus Argostemma Wall. (Rubiaceae) in the Malay Peninsula and Peninsular Thailand are discussed with regard to general morphology, distribution and ecology from studies of herbarium specimens from various herbaria together with the field surveys of the natural populations in the study area

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Species of Argostemma typically inhabit wet, shady areas of primary (undisturbed) evergreen forests, e.g. moss-covered rock faces, stream banks and surroundings of waterfalls (Sridith & Puff 2000, Sridith 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Species of Argostemma typically inhabit wet, shady areas of primary (undisturbed) evergreen forests, e.g. moss-covered rock faces, stream banks and surroundings of waterfalls (Sridith & Puff 2000, Sridith 2007.…”
Section: Introductionmentioning
confidence: 99%
“…During a floristic exploration work in the HonBa Nature Reserve of Khanh Hoa Province in Vietnam, we collected an interesting species of Argostemma which after a close scrutiny of the available literature (Pitard 1823, Ho 2003 appeared somewhat similar to A. bariense by having 5 sepals and 3-4 pairs of opposite leaves, but the glabrous character of our specimen was intriguing, as that character is not seen in any of the previously reported Indo-Chinese Argostemma. Further examination of the morphology and study of some additional literature (Bremer 1989, Sridith 2007, suggested a close affinity with a Bornean species, A. apiculatum. However, examination of the type specimens and protologue showed no complete match with either A. apiculatum or any other earlier described taxa of Argostemma.…”
mentioning
confidence: 95%
“…1). Some other glabrous species have also been reported from Thailand (Puff et al 2005, Sridith 2007) but they are morphologically very different from A. glabra.…”
mentioning
confidence: 97%
See 2 more Smart Citations